"Shake well before using": The dialectics of Michael Silverstein (1945–2020). (5th January 2022) - Inoue, Miyako
Abstract: Michael Silverstein, the Charles F. Grey Distinguished Service Professor of Anthropology, Linguistics, and Psychology at the University of Chicago, passed away on Friday, July 17, 2020, after a year‐long battle with brain cancer. This tribute essay reflects upon Silverstein's distinguished contributions to contemporary linguistic anthropology and sociolinguistics.